Low‐Pressure Radical 11C‐Aminocarbonylation of Alkyl Iodides through Thermal Initiation. Issue 36 (25th November 2016) - Chow, Shiao Y.; Odell, Luke R.; Eriksson, Jonas
Abstract : A radical 11 C‐aminocarbonylation protocol characterized by excellent substrate compatibility was developed to transform alkyl iodides into 11 C‐labelled amides, including the 11β‐HSD1 inhibitor [ carbonyl ‐ 11 C]adamantan‐1‐yl(piperidin‐1‐yl)methanone. This protocol serves as a complementary extension of palladium‐mediated 11 C‐aminocarbonylation, which is limited to the preparation of 11 C‐labelled compounds lacking beta‐hydrogen atoms. The use of AIBN as a radical initiator and a low‐pressure xenon–[ 11 C]CO delivery unit represents a simple and convenient alternative to previous radical 11 C‐carbonylation methodologies burdened with the need for a proprietary high pressure reactor connected to a light source. Abstract : A practical and efficient protocol for the preparation of 11 C‐labelled alkyl amides by using a low‐pressure xenon system is presented. This methodology, based on a thermally initiated radical carbonylation, provides a valuable complement to the transition‐metal‐mediated reaction since it allows the use of non‐activated β‐hydride‐containing substrates.